Analisis Efektivitas Kelompok Tani Terhadap Pendapatan Usahatani Jagung Di Kemelak Bindung Langit Baturaja Timur - Endang Lastinawati; Fadilah, Nur; Rosmawati, Henny; Herdaning Putri, Piranti; Chuzaimah (Jurnal AGRIBIS, 2025)
Corn is a commodity used to meet food needs, raw materials for the feed industry, and other needs, such as alternative fuels (biofuels) and polymers, so its production is expected to continue to increase. Corn productivity is thought to be able to be increased through the role of farmer groups. This study aims to analyze the effectiveness of corn farmer groups and determine the amount of farming income in those groups. The study was conducted in Kemelak Bindung Langit Village, East Baturaja. The research method used was the survey method. The research sample was taken using the census method, namely farmers who are members of three corn farmer groups, from 27 existing farmer groups. The total number of samples from the three farmer groups was 79 farmers. The results of the study showed that corn farmer groups in Kemelak Bindung Langit Village were not effective in their function as providers of corn production facilities, as a medium for transferring knowledge, or as a place to market production results. In terms of income, corn farming in Kemelak Bindung Langit Village generated an income of IDR 11,355,498.00 per planting season